The shifting role of the listeners in the mediamorphosis process of culture radio: A case study of Jodhipati 106.1 FM - Zainal Abidin Achmad; Rachmah Ida (Faculty of Social and Political Science, Universitas Airlangga, 2019)
The adaptation of the use of communication technology towards media convergence (mediamorphosis) makes it a necessity for radio to change. Jodhipati FM, a commercial radio station in Nganjuk Regency which declared its identity as a Javanese cultural radio station, has also made the change. The uniqueness of Jodhipati FM to broadcast 100% Javanese cultural programs originated from the demands of listeners to listen to the wayang kulit (leather puppet) program. The close interaction and relationships between the listeners and radio management has made every change in Jodhipati FM driven by the interests of the listeners. This qualitative research collected data through a virtual ethnography supplemented by participant observation and in-depth interviews with nine informants. The results found there to be a mediamorphosis pattern that explains the stages of Jodhipati FM’s change and the influence of the listeners’ demands, from the early history of its establishment through to the present. At present, Jodhipati FM uses Facebook, streaming and WhatsApp as broadcast support. In interactive engagement between the listeners and radio management in the virtual world, both parties have an equal role as media producers. In the life of a networked society, the listener experiences a shift in role and characteristics. Apart from acting as the media producer, the radio listeners are involved in programming, they are free to criticize and they are also free to look for sponsors and advertisements. The characteristics of the listener have also changed. They become physically visible, their voices are heard, their personalities are revealed, they live in various social networks, age restrictions disappear, there are no territorial boundaries and there are no time limits. As a cultural radio station, Jodhipati FM has the advantage of being able to preserve and spread Javanese culture throughout the world.